In vivo Modulatory Effect of Coffee (Coffea canephora var. Robusta) on the Expression Levels of Murine microRNA‐124‐3p Associated with Antioxidant Defenses. Issue 2 (23rd August 2019) - Curti, Valeria; Verri, Manuela; Baldi, Alessandra; Dacrema, Marco; Masiello, Irene; Dossena, Maurizia; Daglia, Maria
Abstract : Antioxidant activity is one of the most studied properties of coffee as a beverage, and is mainly ascribed to its polyphenol content, although there is limited scientific literature regarding its mechanism of action at the molecular level. In recent years, epigenetics has been featured as a promising approach in many studies for explaining the mechanisms of action involved in its effects on health exerted by foods and food components. To investigate such an epigenetic contribution toward the antioxidant properties of coffee, an in vivo study was performed on healthy C57BL/6 mice fed with a normal diet supplemented with a low‐molecular‐weight (MW) fraction (MW < 3500 Da) obtained from regular and decaffeinated coffee. Regular coffee supplementation induced a downregulation of microRNA‐124‐3p, and its validated target, mRNA coding for glutathione peroxidase (GPX), was upregulated. Decaffeinated coffee was not found to induce any significant changes in the expression levels of microRNA‐124‐3p and its validated target mRNA. It may be concluded from the results that regular intake of coffee exerts its antioxidant activity through an epigenetic mechanism of action, at least in part, being able to influence the expression levels on a miRNA and an mRNA involved in antioxidant defenses, with caffeine playing a crucial role.